2008
DOI: 10.1074/jbc.m804048200
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Basis of Serpin Polymerization Studied by Hydrogen/Deuterium Exchange and Mass Spectrometry

Abstract: The serpinopathies are a group of inherited disorders that share as their molecular basis the misfolding and polymerization of serpins, an important class of protease inhibitors. Depending on the identity of the serpin, conditions arising from polymerization include emphysema, thrombosis, and dementia. The structure of serpin polymers is thus of considerable medical interest. Wild-type ␣ 1 -antitrypsin will form polymers upon incubation at moderate temperatures and has been widely used as a model system for st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 29 publications
6
38
2
1
Order By: Relevance
“…Although we could not analyze the peptides spanning s1C due to the absence of a common peptide between D1, D2, and D3, the current results suggest that ␤-sheet C maintains its structure during complex formation. This is quite a contrast to the recent report of Wintrode and co-workers (39) in which ␤-sheet C appears to be destabilized first during polymerization. Our previous mutational studies on ␣ 1 AT (6) showed that destabilization of ␤-sheet C caused the molecule to convert into the latent form (RSLinserted monomer) and suggested that the integrity of ␤-sheet C is crucial for maintaining the kinetic trap of the native form.…”
Section: D2-specific H/d-ex: Regions Unfolded During the Complexcontrasting
confidence: 99%
See 2 more Smart Citations
“…Although we could not analyze the peptides spanning s1C due to the absence of a common peptide between D1, D2, and D3, the current results suggest that ␤-sheet C maintains its structure during complex formation. This is quite a contrast to the recent report of Wintrode and co-workers (39) in which ␤-sheet C appears to be destabilized first during polymerization. Our previous mutational studies on ␣ 1 AT (6) showed that destabilization of ␤-sheet C caused the molecule to convert into the latent form (RSLinserted monomer) and suggested that the integrity of ␤-sheet C is crucial for maintaining the kinetic trap of the native form.…”
Section: D2-specific H/d-ex: Regions Unfolded During the Complexcontrasting
confidence: 99%
“…The overall H/D-EX level of ␣ 1 AT was slightly higher than that of a previous report (38,39) presumably because of the nonsalt condition of the current H/D-EX study. It was reported that the presence of salts stabilized protein conformation and suppressed H/D-EX (40).…”
Section: D2-specific H/d-ex: Regions Unfolded During the Complexcontrasting
confidence: 86%
See 1 more Smart Citation
“…Endopeptidase cleavage data showed that helix I remained protected from digestion in monomeric Z α 1 -antitrypsin, in polymers of Z α 1 -antitrypsin formed under physiological conditions in vitro and in polymers isolated from the endoplasmic reticulum of hepatocytes of a Z α 1 -antitrypsin homozygote. These data are consistent with hydrogen/deuterium exchange studies that showed no change in the helix I of α 1 -antitrypsin upon formation of the polymerogenic intermediate or chains of polymers (30).…”
Section: Discussionsupporting
confidence: 80%
“…It is likely that this difference is also manifest in intermediate ensembles induced by the two approaches. Indeed, the heatinduced alpha-1 antitrypsin intermediate shows evidence for a more compact state than that observed in 1 M guanidinium hydrochloride (41,42,44). However, regional differences in s5A behavior are similar in both the denaturant-mediated and heat-induced polymerization (Table 2; Figure 4C, right).…”
Section: Discussionmentioning
confidence: 85%